Juan de Valdés, Diálogo de la lengua. A diplomatic edition. ed. by K. Anipa. The Modern Humanities research Association, cambridge, 2014; 133 pp. (Critical Texts, 38). - Máynez, Pilar (Nueva Revista de Filología Hispánica (NRFH), 2016)
Se reseñó el libro: Diálogo de la lengua. A diplomatic edition.